ANALISIS KANDUNGAN UNSUR HARA PUPUK ORGANIK CAIR DARI KOTORAN SAPI DAN DAUN Pueraria javanica - Toto Suryanto; Fandi Julian; Aang Kuvaini (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Cow dung and leaves of Pueraria javanica are organic wastes that highly available and content nutrients. Generally, there is a lot of Pueraria javanica’s leaf waste in oil palm plantations that will have mature period. Both of these wastes could be used as liquid organic fertilizer that has advantage of being easier to apply and could be watered at the same time. It will also more profitable when the application doing in the dry season. The purpose of this study are to obtain alternative organic waste and determine the nutrient content of the best liquid organic fertilizer. This research conducted at PT Rea Kaltim, East Kalimantan, from May to September 2022. This research used a descriptive method consisting of observation, literature study and interviews. Liquid organic fertilizer treatment consisted of 4 mixtures, there are P0 (1 kg of cow dung + 0 kg of Pueraria javanica), P1 (1 kg + 0,25), P2 (1 kg + 0,5 kg), P3 (1 kg + 0,75 kg), and P4 (1 kg + 1 kg). The result of research showed that cow dung and Pueraria javanica could be used as alternative organic materials for the manufacture of liquid organic fertilizer. Based on the results of analysis, the best nutrient content in liquid organic fertilizer was found in the treatment of 1 kg of cow manure and 1 kg of Pueraria javanica with 0,21% nitrogen, 0,12% phosphorus and 0,20% potassium.